Constructing empathy through language: a linguistic perspective on compassionate communication in mental health services - Youstiana Dwi Rusita (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Mental health disorders affect hundreds of millions globally, and evidence increasingly indicates that perceived empathy in therapeutic communication significantly shapes alliance formation, adherence, and clinical outcomes. Objective: This study aims to examine how empathy is linguistically constructed and interactionally organized across face-to-face counseling, outpatient psychiatry, and tele-mental health contexts. Method: Using a qualitative corpus-based design integrating Conversation Analysis, Appraisal Theory, and discourse-pragmatic stance analysis, this research analyzes 40 therapeutic sessions, practitioner interviews, and institutional communication guidelines. Results: The findings reveal recurrent sequential architectures in which patient disclosure is followed by calibrated pauses, affective acknowledgment, and reformulative expansion that promote narrative elaboration. Linguistic markers of affect, engagement, and graduation systematically co-occur to construct emotional alignment while mitigating stigma and identity threat. A solidarity–authority continuum further demonstrates that compassion is dynamically negotiated through pronoun ecology and modality shifts rather than expressed as a static interpersonal trait. Implication: These findings suggest that empathy in therapeutic settings is not an inherent trait but a dynamically constructed discourse practice that can be systematically trained to improve alliance, reduce stigma, and enhance clinical outcomes. Novelty: The novelty of this study lies in advancing a multidimensional linguistic framework that operationalizes empathy as a structured, measurable, and computationally traceable discourse phenomenon within mental health services.